Community governance in primary health care: towards an international Ideal Type. (27th May 2016) - Meads, Geoffrey; Russell, Grant; Lees, Amanda
Summary: Against a global background of increased resource management responsibilities for primary health care agencies, general medical practices, in particular, are increasingly being required to demonstrate the legitimacy of their decision making in market oriented environments. In this context a scoping review explores the potential utility for health managers in primary health care of community governance as a policy concept. The review of recent research suggests that applied learning from international health systems with enhanced approaches to public and patient involvement may contribute to meeting this requirement. Such approaches often characterise local health systems in Latin America and North West Europe where innovative models are beginning to respond effectively to the growing demands on general practice. The study design draws on documentary and secondary data analyses to identify common components of community governance from the countries in these regions, supplemented by other relevant international studies and sources where appropriate. Within a comprehensive framework of collaborative governance the components are aggregated in an Ideal Type format to provide a point of reference for possible adaptation and transferable learning across market oriented health systems. Each component is illustrated with international exemplars from recent organisational practices in primary health care. The application of community governance is considered for the particular contexts of GP led Clinical Commissioning Groups in England and Primary Health Networks in Australia. Some components of the Ideal Type possess potentially powerful negative as well as positive motivational effects, with PPI at practice levels sometimes hindering the development of effective local governance. This highlights the importance of careful and competent management of the growing resources attributed to primary health care agencies, which possess an increasingly diverse range of non‐governmental status. Future policy and research priorities are outlined. Copyright © 2016 John Wiley & Sons, Ltd.